Analysis of three-phase rectifier systems with controlled DC-link current under unbalanced grids - Kumar, D.; Davari, P.; Zare, Firuz; Blaabjerg, F. (2017)
© 2017 IEEE. Voltage unbalance is the most common disturbance in distribution networks, which gives undesirable effects on many grid connected power electronics systems including Adjustable Speed Drive (ASD). Severe voltage unbalance can force conventional three-phase diode rectifiers into almost single-phase operation, which degrades the grid power quality and also imposes a significant negative impact on the ASD system. This major power quality issue affecting the conventional rectifiers can be attenuated by controlling the DC-link current based on an Electronic Inductor (EI) technique. The purpose of this paper is to analyze and compare the performance of an EI with a conventional three-phase rectifier under unbalanced grid conditions. Experimental and simulation results validate the proposed mathematical modeling.